Accessory mitral valve tissue causing left ventricular outflow tract obstruction. - Meldrum-Hanna, W G (1986)
Although left ventricular outflow tract obstruction is commonly associated with congenitally corrected transposition of the great vessels, this obstruction is seldom caused by accessory mitral valve tissue. Three cases in which accessory mitral valve tissue caused left ventricular outflow tract obstruction in children are described. Two had congenitally corrected transposition and one had normally connected great vessels. The accessory leaflet tissue, which was identified by echocardiography and angiography, was attached by chordae tendineae to normally sited papillary muscles and herniated into the left ventricular outflow tract during systole. Operation was successful in these patients. The accessory valve tissue was excised via an arteriotomy in the great vessel that arose from the left ventricle. The obstructive tissue was excised close to its peripheral attachments in the outflow tract and its chordae tendineae were divided. Resection was performed without injury to the abnormally placed conduction system or to the normal valve structures.